Two pseudo‐enantiomeric forms of N‐benzyl‐4‐hydroxy‐1‐methyl‐2, 2‐dioxo‐1H‐2λ6, 1‐benzothiazine‐3‐carboxamide and their analgesic properties. Issue 5 (14th April 2016) - Ukrainets, Igor V.; Shishkina, Svitlana V.; Baumer, Vyacheslav N.; Gorokhova, Olga V.; Petrushova, Lidiya A.; Sim, Galina
Abstract : Two pseudo‐enantiomeric forms of N ‐benzyl‐4‐hydroxy‐1‐methyl‐2, 2‐dioxo‐1 H ‐2λ 6, 1‐benzothiazine‐3‐carboxamide have been crystallized from different solvents. A pharmacological study has shown that the analgesic effect of form A (from methylene chloride) is almost four times as high as that of form B (from N, N ‐dimethylformamide, ethanol, ethyl acetate or xylene). Abstract : The fact that molecular crystals exist as different polymorphic modifications and the identification of as many polymorphs as possible are important considerations for the pharmaceutic industry. The molecule of N ‐benzyl‐4‐hydroxy‐1‐methyl‐2, 2‐dioxo‐1 H ‐2λ 6, 1‐benzothiazine‐3‐carboxamide, C17 H16 N2 O4 S, does not contain a stereogenic atom, but intramolecular hydrogen‐bonding interactions engender enantiomeric chiral conformations as a labile racemic mixture. The title compound crystallized in a solvent‐dependent single chiral conformation within one of two conformationally polymorphic P 21 21 21 orthorhombic chiral crystals (denoted forms A and B ). Each of these pseudo‐enantiomorphic crystals contains one of two pseudo‐enantiomeric diastereomers. Form A was obtained from methylene chloride and form B can be crystallized from N, N ‐dimethylformamide, ethanol, ethyl acetate or xylene. Pharmacological studies with solid–particulate suspensions have shown that crystalline form A exhibits an almost fourfold higher antinociceptive activity compared to form B .